Meta‐analysis of benefits of portal–superior mesenteric vein resection in pancreatic resection for ductal adenocarcinoma. Issue 3 (10th December 2015) - Giovinazzo, F.; Turri, G.; Katz, M. H.; Heaton, N.; Ahmed, I.
Abstract : Background: Pancreatic ductal adenocarcinoma has a poor prognosis without surgery. No standard treatment has yet been accepted for patients with portal–superior mesenteric vein (PV‐SMV) infiltration. The present meta‐analysis aimed to compare the results of pancreatic resection with PV‐SMV resection for suspected infiltration with the results of surgery without PV‐SMV resection. Methods: A systematic search was performed of PubMed, Embase and the Cochrane Library in accordance with PRISMA guidelines from the time of inception to 2013. The inclusion criteria were comparative studies including patients who underwent pancreatic resection with or without PV‐SMV resection. One, 3‐ and 5‐year survival were the primary outcomes. Results: Twenty‐seven studies were identified involving a total of 9005 patients (1587 in PV‐SMV resection group). Patients undergoing PV‐SMV resection had an increased risk of postoperative mortality (risk difference (RD) 0·01, 95 per cent c.i. 0·00 to 0·03; P = 0·02) and of R1/R2 resection (RD 0·09, 0·06 to 0·13; P < 0·001) compared with those undergoing standard surgery. One‐, 3‐ and 5‐year survival were worse in the PV‐SMV resection group: hazard ratio 1·23 (95 per cent c.i. 1·07 to 1·43; P = 0·005), 1·48 (1·14 to 1·91; P = 0·004) and 3·18 (1·95 to 5·19; P < 0·001) respectively. Median overall survival was 14·3 months for patients undergoing pancreatic resection with PV‐SMV resection and 19·5 months for those without vein resection ( P = 0·063). Neoadjuvant therapies recently showed promising results. Conclusion: This meta‐analysis showed increased postoperative mortality, higher rates of non‐radical surgery and worse survival after pancreatic resection with PV‐SMV resection. This may be related to more advanced disease in this group. Abstract : Worse outcome with vein resection